Closely related parasitic plants have similar host requirements and related effects on hosts. Issue 17 (31st July 2021) - Matthies, Diethart
Abstract: The performance of root hemiparasites depends strongly on host species identity, but it remains unknown whether there exist general patterns in the quality of species as hosts for hemiparasites and in their sensitivity to parasitism. In a comparative approach, the model root hemiparasites Rhinanthus minor and R. alectorolophus were grown with 25 host species (grasses, forbs, and legumes) at two nutrient levels. Hosts grown without parasites served as a control. Host species identity strongly influenced parasite biomass and other traits, and both parasites grew better with legumes and grasses than with forbs. The biomass of R. alectorolophus was much higher than that of R. minor with all host plants and R. alectorolophus responded much more strongly to higher nutrient availability than R. minor . The performance of the two species of Rhinanthus with individual hosts was strongly correlated, and it was also correlated with that of R. alectorolophus and the related Odontites vulgaris in previous experiments with many of the same hosts, but only weakly with that of the less closely related Melampyrum arvense . The negative effect of R. minor on host biomass was less strong than that of R. alectorolophus, but stronger relative to its own biomass, suggesting that it is more parasitic. The impact of the two parasites on individual hosts did not depend on nutrient level and was correlated. Several legumes and grasses were tolerant of parasitism. While R. minor slightly reduced mean overall productivity, R. alectorolophus increased it with several species, indicating that the loss of host biomass was more than compensated by that of the parasite. The results show that closely related parasites have similar host requirements and correlated negative effects on individual hosts, but that there are also specific interactions between pairs of parasitic plants and their hosts. Abstract : I found that the performance of the two hemiparasites Rhinanthus minor and R. alectorolophus grown with 25 host species was correlated; that is, plant species that were good hosts for R. alectorolophus were also good hosts for R. minor . The performance of the Rhinanthus species with the individual host species was also correlated with that of Rhinanthus in previous experiments with many of the same hosts and with that of the closely related parasites Odontites vulgaris, but not with that of the less closely related Melampyrum arvense . The results show that closely related parasites have similar host requirements and have correlated negative effects on individual hosts, but that there are also specific interactions between pairs of parasitic plants and their hosts that will result in different impacts on host communities.